A high-strength wood pulp fiber paper and its preparation method and application

By using high-strength wood pulp fiber paper in the base paper of the paper-core copper clad substrate, the problem of insufficient strength of the base paper is solved, and dimensional stability and mechanical performance are improved in high-temperature environments, which are suitable for the manufacturing of copper clad plates.

CN119308181BActive Publication Date: 2025-04-18JIANTAO FOGANG INSULATION MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411695433.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The substrate strength of the existing paper-core copper-clad substrate is insufficient, and it is impossible to maintain dimensional stability in high temperature environments, which affects the flatness and reliability of the circuit board.

Method used

High-strength wood pulp fiber paper is used, and the preparation method includes treating wood pulp and cotton lint pulp using a pulp machine and a beating device, adding flame retardant and specific ratio reinforcers (cellulose nanofibers, sodium alginate, calcium chloride and myristic acid), forming a reinforcement coating by impregnation and drying.

Benefits of technology

The tensile and wet tensile strength of the base paper is improved, and the mechanical and heat resistance of the base paper is enhanced, making it suitable for copper clad plate manufacturing in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151971330000071
    Figure BDA0005151971330000071
Patent Text Reader

Abstract

The present invention relates to a high-strength wood pulp fiber paper and a preparation method and application thereof, belonging to the technical field of papermaking. The high-strength wood pulp fiber paper is obtained by immersing base paper in a reinforcing agent solution and then forming a reinforcing coating on the surface of the base paper. The sodium alginate and cellulose nanofibers in the reinforcing agent are cross-linked under the action of calcium chloride to form a three-dimensional network structure, and are filled into the microporous structure of the base paper fiber, effectively improving the tensile properties of the base paper, and the filling of myristic acid makes the sodium alginate / cellulose nanofiber network more densely structured, thereby further improving the strength of the base paper. The components in the reinforcing agent promote each other and synergistically improve the mechanical strength and other properties of the base paper. Based on the high-strength characteristics of the fiber paper, it can be used as a reinforcing material for preparing copper clad laminates or prepregs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking, and in particular to high-strength wood pulp fiber paper and a preparation method and application thereof. Background Art

[0002] Paper core copper clad substrate uses impregnated fiber paper as reinforcement material. After the fiber paper is impregnated with resin solution and dried, it is covered with glue-coated electrolytic copper foil and finally pressed and formed under high temperature and high pressure. Its production process mainly includes four major processes: synthesis and preparation of resin glue, impregnation and drying of semi-finished products, lamination and cutting and packaging. With the development trend of high density, multi-function and "light, thin and small" electronic devices, the performance requirements for paper core copper clad substrates are getting higher and higher.

[0003] The reinforcing materials of paper core copper clad laminates can be paper or cloth, which determine the mechanical properties of the substrate, such as resistance to solder immersion and bending strength. If the base paper is not strong enough, it may not be able to withstand a long-term high temperature environment, resulting in a decrease in heat resistance. This will affect the application of copper clad laminates in high temperature environments, such as welding during SMT (surface mount technology). In addition, base paper with insufficient strength is prone to deformation and warping under high temperature and pressure, which will lead to poor dimensional stability of the copper clad laminate, affect the flatness and reliability of the circuit board, and further affect the assembly and performance of electronic equipment. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-strength wood pulp fiber paper and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a method for preparing high-strength wood pulp fiber paper, comprising the following steps:

[0007] S1. pulverizing bleached eucalyptus pulp and cotton linter pulp with a pulper to obtain pulverized pulp; beating the pulverized pulp with a deflaker and a disc refiner, and adding a flame retardant to the pulverized pulp to obtain qualified pulp; removing slag from the qualified pulp through a three-stage deslagging pump system to obtain deslagging pulp; cooling and diluting the deslagging pulp through a white water tower, and sending the cooled pulp to a pressure screen for purification and screening with a pulp flushing pump to obtain purified pulp with a pulp concentration of 3-5%; processing the purified pulp through a stabilizing box and a front box to obtain a pulp on the net; processing the pulp on the net through pressing and drying to obtain base paper; wherein the mass ratio of bleached eucalyptus pulp to cotton linter pulp is (2-5):1;

[0008] S2. The base paper is immersed in an aqueous solution of a reinforcing agent and then dried to obtain the high-strength wood pulp fiber paper; wherein the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:(0.2-0.6):(0.1-0.3):1; the concentration of the reinforcing agent in the aqueous solution of the reinforcing agent is 40-60wt%, and the mass ratio of the aqueous solution of the reinforcing agent to the base paper is (2-3):1.

[0009] Specifically, the sodium alginate and cellulose nanofibers in the reinforcing agent are cross-linked under the action of calcium chloride to form a three-dimensional network structure, which is filled into the microporous structure of the base paper fiber, effectively improving the tensile properties of the base paper. The long carbon chain of myristic acid can penetrate into the network of sodium alginate and cellulose nanofibers, increasing the density of the network through physical entanglement. At the same time, myristic acid has good thermal stability and can maintain its physical and chemical properties under high temperature conditions, which helps to improve the thermal stability and durability of the cross-linked network.

[0010] Preferably, in step S1, the whiteness of the bleached eucalyptus pulp is ≥90%; the α-cellulose of the cotton linter pulp is ≥95wt%, the ash content is ≤0.3wt%, and the whiteness is ≥85%.

[0011] Preferably, in step S1, the beating method is that the deflaker and two disc refiners are connected in series to perform semi-free beating on the fragmented pulp.

[0012] Preferably, in step S1, the flame retardant is a magnesium hydroxide flame retardant, the magnesium hydroxide flame retardant has a Mg(OH)2 content of ≥95%, and a particle size D 50 ≤2μm; the mass ratio of flame retardant to crushed pulp is (0.05-0.1):1.

[0013] Preferably, in step S1, the average length of the cotton fiber and the wood pulp fiber in the qualified pulp is 0.8-1 mm, the beating degree of the qualified pulp is controlled between 20-24°SR, and the wet weight of the fiber is 1.8-2.3 g.

[0014] Preferably, in the process of the purified slurry passing through the stabilizing box and the head box in step S1, the ratio of the slurry conveying rate to the head box conveying rate is (1-1.05):1, the shaking amplitude in the head box is 0.8-1.2mm, and the vibration frequency is 180-230 times / min.

[0015] Preferably, in step S1, the moisture content of the base paper is 4.0-5.5%.

[0016] Preferably, in step S2, the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1: (0.4-0.5): (0.2-0.3): 1. Most preferably, the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1: 0.5: 0.2: 1.

[0017] Preferably, in step S2, the immersion temperature is 30-40°C and the immersion time is 30-60 min.

[0018] Preferably, in step S2, the drying temperature is 80-100°C and the drying time is 5-10 minutes.

[0019] In a second aspect, the present invention provides a high-strength wood pulp fiber paper prepared by the method for preparing the high-strength wood pulp fiber paper described in the first aspect.

[0020] In a third aspect, the present invention provides a use of the high-strength wood pulp fiber paper described in the first aspect or the second aspect in preparing copper-clad laminate base paper, that is, the high-strength wood pulp fiber paper of the present invention can be used as a reinforcing material for preparing copper-clad laminates or prepregs.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The high-strength wood pulp fiber paper of the present invention is obtained by impregnating base paper in a reinforcing agent solution, and then forming a reinforcing coating on the surface of the base paper. The sodium alginate and cellulose nanofibers in the reinforcing agent are cross-linked with each other under the action of calcium chloride to form a three-dimensional network structure, and are filled into the microporous structure of the base paper fiber, effectively improving the tensile properties of the base paper, and the filling of myristic acid makes the sodium alginate / cellulose nanofiber network more compact, thereby further improving the strength of the base paper, so the components in the reinforcing agent promote each other and jointly improve the strength performance of the base paper. And because the reinforcing agent fills the micropores in the base paper to prevent water from penetrating into the interior, it can also improve the wet tensile strength. Based on the high-strength characteristics of fiber paper, it can be used as a reinforcing material for preparing copper-clad laminates or prepregs.

[0023] (2) The present invention uses bio-based polymers to replace petroleum-based plastics as reinforcing agents, which has the advantages of being safe, environmentally friendly, and biodegradable. DETAILED DESCRIPTION

[0024] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0025] The sources of reagents used in the following examples and comparative examples are as follows:

[0026] Cellulose nanofibers: particle size is 3-10 nm, the manufacturer is Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., brand name is lnb-1130;

[0027] Flame retardant: magnesium hydroxide flame retardant, Mg(OH)2 content ≥95%, particle size D 50 ≤2μm, whiteness ≤90%, purchased from Weifang Haililong Magnesium Industry Co., Ltd.

[0028] Example 1

[0029] A method for preparing high-strength wood pulp fiber paper comprises the following steps:

[0030] S1. pulverize bleached eucalyptus pulp and cotton linter pulp with a pulper to obtain pulverized pulp; use a deflaker and a disc refiner to beat the pulverized pulp, and add a flame retardant to the pulverized pulp to obtain qualified pulp; remove the qualified pulp through a three-stage deslagging pump system to obtain deslagging pulp; the deslagging pulp is cooled and diluted through a white water tower, and the cooled pulp is sent to a pressure screen for purification and screening by a pulp flushing pump to obtain purified pulp with a pulp concentration of 4%; the purified pulp is processed by a stabilizing box and a front box to obtain a pulp on the net; the pulp on the net is subjected to pressing and drying to obtain base paper; wherein the mass ratio of the bleached eucalyptus pulp to the cotton linter pulp is 3:1;

[0031] The whiteness of the bleached eucalyptus pulp is ≥90%; the α-cellulose of the cotton linter pulp is ≥95wt%, the ash content is ≤0.3wt%, and the whiteness is ≥85%; the pulping method is that a deflaker and two disc refiners are connected in series to perform semi-free pulping on the crushed pulp; the mass ratio of the flame retardant to the crushed pulp is 0.06:1; the average length of the cotton fiber and the wood pulp fiber in the qualified pulp is 1mm, the beating degree of the qualified pulp is 20°SR, and the wet weight of the fiber is 2.0g; in the process of the purified pulp passing through the stabilizing box and the head box, the ratio of the pulp conveying rate to the net conveying rate is 1:1, the shaking amplitude in the head box is 1mm, and the vibration frequency is 200 times / min; the moisture content of the base paper is 5.0%.

[0032] S2. Place the base paper in an aqueous solution of a reinforcing agent and immerse it at 35°C for 40 minutes. After taking it out, dry it at 95°C for 10 minutes to obtain the high-strength wood pulp fiber paper; wherein the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:0.5:0.2:1, the concentration of the reinforcing agent in the aqueous solution of the reinforcing agent is 55wt%, and the mass ratio of the aqueous solution of the reinforcing agent to the base paper is 2.5:1.

[0033] Example 2

[0034] A method for preparing high-strength wood pulp fiber paper comprises the following steps:

[0035] S1. Using a pulper to crush bleached eucalyptus pulp and cotton linter pulp to obtain crushed pulp; using a deflaker and a disc refiner to beat the crushed pulp, and adding a flame retardant to the crushed pulp to obtain qualified pulp; passing the qualified pulp through a three-stage deslagging pump system to deslagging, to obtain deslagging pulp; the deslagging pulp is cooled and diluted through a white water tower, and the cooled pulp is sent to a pressure screen for purification and screening by a pulp flushing pump to obtain purified pulp with a pulp concentration of 3%; the purified pulp is processed by a stabilizing box and a front box to obtain a pulp on the net; the pulp on the net is subjected to pressing and drying to obtain base paper; wherein the mass ratio of the bleached eucalyptus pulp to the cotton linter pulp is 2:1;

[0036] Among them, the whiteness of the bleached eucalyptus pulp is ≥90%; the α-cellulose of the cotton linter pulp is ≥95wt%, the ash content is ≤0.3wt%, and the whiteness is ≥85%; the pulping method is that a deflaker and two disc refiners are connected in series to perform semi-free pulping on the crushed pulp; the mass ratio of the flame retardant to the crushed pulp is 0.05:1; the average length of the cotton fiber and the wood pulp fiber in the qualified pulp is 0.8mm, the beating degree of the qualified pulp is 20°SR, and the wet weight of the fiber is 1.8g; in the process of the purified pulp passing through the stabilizing box and the head box, the ratio of the pulp conveying rate to the net conveying rate is 1:1, the shaking amplitude in the head box is 0.8mm, and the vibration frequency is 180 times / min; the moisture content of the base paper is 4.0%.

[0037] S2. Place the base paper in an aqueous solution of a reinforcing agent and immerse it at 30°C for 60 minutes, take it out and dry it at 80°C for 10 minutes to obtain the high-strength wood pulp fiber paper; wherein the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:0.2:0.1:1, the concentration of the reinforcing agent in the aqueous solution of the reinforcing agent is 40wt%, and the mass ratio of the aqueous solution of the reinforcing agent to the base paper is 2:1.

[0038] Example 3

[0039] A method for preparing high-strength wood pulp fiber paper comprises the following steps:

[0040] S1. pulverize bleached eucalyptus pulp and cotton linter pulp by a pulper to obtain pulverized pulp; beat the pulverized pulp by a deflaker and a disc refiner, and add a flame retardant to the pulverized pulp to obtain qualified pulp; remove the qualified pulp by a three-stage deslagging pump system to obtain deslagging pulp; cool and dilute the deslagging pulp by a white water tower, and use a pulp flushing pump to send the cooled pulp to a pressure screen for purification and screening to obtain purified pulp with a pulp concentration of 5%; the purified pulp is processed by a stabilizing box and a front box to obtain a pulp on the net; the pulp on the net is subjected to pressing and drying to obtain base paper; wherein the mass ratio of the bleached eucalyptus pulp to the cotton linter pulp is 5:1;

[0041] Among them, the whiteness of the bleached eucalyptus pulp is ≥90%; the α-cellulose of the cotton linter pulp is ≥95wt%, the ash content is ≤0.3wt%, and the whiteness is ≥85%; the pulping method is that a deflaker and two disc refiners are connected in series to perform semi-free pulping on the crushed pulp; the mass ratio of the flame retardant to the crushed pulp is 0.1:1; the average length of the cotton fiber and the wood pulp fiber in the qualified pulp is 1mm, the beating degree of the qualified pulp is 24°SR, and the wet weight of the fiber is 2.3g; in the process of the purified pulp passing through the stabilizing box and the head box, the ratio of the pulp conveying rate to the net conveying rate is 1.05:1, the shaking amplitude in the head box is 1.2mm, and the vibration frequency is 230 times / min; the moisture content of the base paper is 5.5%.

[0042] S2. Place the base paper in an aqueous solution of a reinforcing agent and immerse it at 40°C for 30 minutes. After taking it out, dry it at 80°C for 5 minutes to obtain the high-strength wood pulp fiber paper; wherein the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:0.6:0.3:1, the concentration of the reinforcing agent in the aqueous solution of the reinforcing agent is 60wt%, and the mass ratio of the aqueous solution of the reinforcing agent to the base paper is 3:1.

[0043] Example 4

[0044] The difference between Example 4 and Example 1 is that the total amount of the reinforcing agent remains unchanged, and the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:0.4:0.3:1.

[0045] Comparative Example 1

[0046] The difference between Comparative Example 1 and Example 1 is that the base paper of Comparative Example 1 is not impregnated with the aqueous solution of the reinforcing agent.

[0047] Comparative Example 2

[0048] The difference between Comparative Example 2 and Example 1 is that the total amount of reinforcing agent remains unchanged, cellulose nanofibers are not added, and the missing amount is made up by sodium alginate, calcium chloride and myristic acid in a mass ratio of 0.5:0.2:1.

[0049] Comparative Example 3

[0050] The difference between Comparative Example 3 and Example 1 is that the total amount of the reinforcing agent remains unchanged, sodium alginate is not added, and the missing amount is made up by cellulose nanofibers, calcium chloride and myristic acid in a mass ratio of 1:0.2:1.

[0051] Comparative Example 4

[0052] The difference between Comparative Example 4 and Example 1 is that the total amount of the reinforcing agent remains unchanged, calcium chloride is not added, and the missing amount is made up by cellulose nanofibers, sodium alginate and myristic acid in a mass ratio of 1:0.5:1.

[0053] Comparative Example 5

[0054] The difference between Comparative Example 5 and Example 1 is that the total amount of the reinforcing agent remains unchanged, myristic acid is not added, and the missing amount is made up by cellulose nanofibers, sodium alginate and calcium chloride in a mass ratio of 1:0.5:0.2.

[0055] Comparative Example 6

[0056] The difference between Comparative Example 6 and Example 1 is that the total amount of the reinforcing agent remains unchanged, and the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 0.5:1:0.2:1.

[0057] Comparative Example 7

[0058] The difference between Comparative Example 7 and Example 1 is that the myristic acid in the enhancer is replaced by stearic acid.

[0059] Comparative Example 8

[0060] The difference between Comparative Example 8 and Example 1 is that the myristic acid in the enhancer is replaced by lauric acid.

[0061] Performance Testing

[0062] The base papers of Examples 1-4 and Comparative Examples 1-8 were respectively subjected to tensile strength tests according to GB / T 12914-91 "Determination of tensile strength of paper and paperboard (constant rate stretching method)", and transverse and longitudinal wet strength tests were performed according to the method of GB / T 24328.4-2020 "Sanitary paper and its products Part 4: Determination of wet tensile strength". Each group of samples was placed in an oven at 130°C, and the state of each group of samples was observed. When the sample showed obvious color changes and physical property degradation (such as deformation, rupture, etc.), the timing was stopped and the heat resistance time was recorded. See Table 1 for details.

[0063] Table 1 Mechanical strength data of each group of samples

[0064]

[0065] As shown in Table 1, by comparing Example 1 with Comparative Examples 1-5, it can be seen that the reinforcing agent of the present invention has a relatively significant improvement in the tensile strength and wet strength of the base paper, indicating that the four components of sodium alginate, cellulose nanofibers, calcium chloride and myristic acid in the reinforcing agent promote each other and synergistically improve the strength performance of the base paper. In addition, the cross-linked network formed by the reinforcing agent fills the micropores in the base paper to prevent water from penetrating into the interior, so it can also improve the wet tensile strength.

[0066] By comparing Example 1 with Comparative Example 6, it can be determined that when the mass ratio of the composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in the reinforcing agent is in the range of 1:(0.2-0.6):(0.1-0.3):1, the mechanical strength of the base paper can reach a better level.

[0067] It can be seen from Example 1 and Comparative Example 7 that the effect of adding myristic acid (tetradecanoic acid) is better than that of adding stearic acid (octadecanoic acid), which may be because the carbon chain of myristic acid (tetradecanoic acid) is shorter than that of stearic acid (octadecanoic acid), and the shorter carbon chain may provide better flexibility and tighter crosslinking points in the crosslinked network, thereby helping them to interact with sodium alginate and cellulose nanofibers, thereby improving the mechanical properties and heat resistance of the material; it can be seen from Example 1 and Comparative Example 8 that myristic acid has better thermal stability than lauric acid (dodecanoic acid), so it may be more able to maintain the stability of the crosslinked network of sodium alginate and cellulose nanofibers under high temperature environment, which helps to extend the service life and performance of the material. The present invention selects myristic acid to make the fiber paper have high strength and good heat resistance at the same time.

[0068] In summary, in the fiber paper preparation method of the present invention, a high-strength wood pulp fiber paper is obtained by adding a reinforcing agent in a specific dosage ratio to impregnate the base paper. Moreover, bio-based polymers are used as reinforcing agents instead of petroleum-based plastics, which has the advantages of safety, environmental protection, and biodegradability.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing high-strength wood pulp fiber paper, characterized in that: The following steps are involved: S1. pulverize bleached eucalyptus pulp and cotton linter pulp by a pulper to obtain pulverized pulp; beat the pulverized pulp by a deflaker and a disc refiner, and add a flame retardant to the pulverized pulp to obtain qualified pulp; remove the qualified pulp by a three-stage deslagging pump system to obtain deslagging pulp; cool and dilute the deslagging pulp by a white water tower, and use a pulp flushing pump to send the cooled pulp to a pressure screen for purification and screening to obtain purified pulp with a pulp concentration of 3-5%; process the purified pulp by a stabilizing box and a front box to obtain a pulp on the net; process the pulp on the net by pressing and drying to obtain base paper; wherein the mass ratio of the bleached eucalyptus pulp to the cotton linter pulp is (2-5):1; S2. The base paper is immersed in an aqueous solution of a reinforcing agent and then dried to obtain the high-strength wood pulp fiber paper; wherein the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1: (0.2-0.6): (0.1-0.3): 1; the concentration of the reinforcing agent in the aqueous solution of the reinforcing agent is 40-60wt%, and the mass ratio of the aqueous solution of the reinforcing agent to the base paper is (2-3): 1; the immersion temperature is 30-40°C, and the time is 30-60min.

2. The method for preparing high-strength wood pulp fiber paper according to claim 1, characterized in that: In step S2, the reinforcing agent is a composition of cellulose nanofibers, sodium alginate, calcium chloride and myristic acid in a mass ratio of 1:(0.4-0.5):(0.2-0.3):

1.

3. The method for preparing high-strength wood pulp fiber paper according to claim 1, characterized in that: In step S1, the whiteness of the bleached eucalyptus pulp is ≥90%; the α-cellulose of the cotton linter pulp is ≥95wt%, the ash content is ≤0.3wt%, and the whiteness is ≥85%; the pulping method is to use a deflaker and two disc refiners in series to perform semi-free pulping on the crushed pulp; the flame retardant is a magnesium hydroxide flame retardant, the Mg(OH)2 content of the magnesium hydroxide flame retardant is ≥95%, and the particle size D 50 ≤2μm; the mass ratio of flame retardant to crushed pulp is (0.05-0.1):1; the average length of cotton fiber and wood pulp fiber in the qualified pulp is 0.8-1mm, the beating degree of qualified pulp is 20-24°SR, and the fiber wet weight is 1.8-2.3g; in the process of the purified pulp passing through the stabilizing box and the net head box, the ratio of the pulp conveying rate to the net conveying rate is (1-1.05):1, the shaking amplitude in the net head box is 0.8-1.2mm, and the vibration frequency is 180-230 times / min; the moisture content of the base paper is 4.0-5.5%.

4. The method for preparing high-strength wood pulp fiber paper according to claim 1, characterized in that: In step S2, the drying temperature is 80-100°C and the drying time is 5-10 minutes.

5. A high-strength wood pulp fiber paper, characterized in that: The high-strength wood pulp fiber paper is prepared by the preparation method of any one of claims 1 to 4.

6. Use of the high-strength wood pulp fiber paper described in claim 5 in the preparation of copper-clad laminate base paper.

Citation Information

Patent Citations

  • Surface sizing agent and preparation method thereof and sizing paper

    CN104711896A

  • High-heat-sealing-strength and high-barrier-property coating and preparation method thereof

    CN116285683A

  • Heat-resistant flexible laminated board base paper and preparation method thereof

    CN117211105A